Ο Κονδυλάκης και το χρονογράφημα. - Σκοπετέας, Σταύρος Χ., 1908-1958 (Βασική βιβλιοθήκη / Αετός, 1956)
Χρονογράφοι: Γεώργιος Τσοκόπουλος -- Δημήτριος Ταγκόπουλος -- Αλέξανδρος Μωραϊτίδης -- Κωνσταντίνος Σκόκος -- Κωστής Χαιρόπουλος -- Ανδρέας Χρυσάνθης -- Μπάμπης Αννινος -- Θεόδωρος Βελλιανίτης -- Κώστας Ουράνης -- Γρηγόριος Ξενόπουλος -- Κωστής Παλαμάς